FRI0102 The significance of serum iga in rheumatoid arthritis in the era of biologic therapy. (23rd January 2014) - Nakashima, A.; Takeshi, Z.; Ogane, K.; Yamada, K.; Kawano, M.; Yachie, A.
Abstract : Background: It is reported that patients with rheumatoid arthritis (RA) have increased IgA concentrations that are related to disease activity 1) . However, since the introduction of biologic therapy, few studies have been published on the significance of serum IgA levels in RA patients. Objectives: To evaluate the significance of serum IgA in RA in the era of biologic therapy. Methods: We enrolled 84 RA patients (70 females, 14 males; mean age 60.5±13.2 years; disease duration 9.7±9.8 years). Patients treated with tocilizumab and abatacept were excluded from this study. We measured IgG, IgA, IgM, C3, C4, CH50, RF, anti-nuclear antibodies, anti-double-strand DNA antibodies, MMP-3, KL-6, and IL-6 in the sera, urinary proteins, urinary blood, and urinary casts and evaluated disease activity score (DAS) 28-CRP, DAS28-ESR, and presence of lung involvement. Then we analyzed the relationships between serum IgA and these clinical parameters. Results: Thirty-five (41.7%) patients were treated with anti-TNF therapy. Mean serum IgA, IgA/C3 ratio and IL-6 were 282.4 ± 126.6 mg/dl, 2.9 ± 1.4, 6.7 ± 15.3 pg /mL, respectively. Nine (10.7%) patients showed serum IgA level equal to or greater than 450 mg/dl, 32 (38.1%) patients IgA/C3 ratio 3, 28 (33.3%) patients IL-6 1 pg /mL, with each of these values defined as elevated. There were no significant differences in any parameters including serum IgA level between patients treated with or without biologic therapy. Mean DAS28-CRP and DAS28-ESR were 2.3±0.9 and 3.0 ±1.1 respectively. We detected significant positive correlations between serum IgA with both CRP and ESR (p<0.01), but not with DAS28-CRP or DAS28-ESR. Eleven (13.1%) patients with proteinuria showed higher serum IgA levels, but without significance (335.6 ± 162.3 vs. 274.4 ± 119.7, p=0.1365) and higher IgA/C3 ratio, but without significance (3.6 ± 1.0 vs. 2.8 ± 1.3, p=0.0849). Four (44.4%) of 9 patients with elevated IgA and 7 (9.3%) of 75 patients without it had proteinuria (p<0.01, chi-square). Five (55.5%) of 9 patients with elevated IgA and 20 (26.6%) of 75 patients without it had lung involvement (p=0.0733, chi-square). Twenty-five (29.8%) patients with lung involvement an elevated higher serum IL-6 level, but without significance (10.8 ± 12.6 vs. 5.00 ± 20.00, p=0.1125). Fourteen (56.0%) of 25 patients with lung involvement and 14 (23.7%) of 59 without it showed elevated serum IL-6 level (p<0.01, chi-square). Conclusions: Some RA patients still have increased serum IgA levels even in the era of biologic therapy, which does not affect the serum IgA levels. The increased serum IgA concentration is related to serological parameters of inflammation. The increased serum IgA concentration is also related to proteinuria and lung involvement, possibly indicating that increased serum IgA concentration is an extra-articular manifestation reflecting involvement of the mucosal immune system in RA patients. Measurement of serum IgA serves to evaluate extra-articular manifestations and is useful in RA patients even in the era of biologic therapy. References: Jorgensen C, Bologna C, Gutierrez M, Anaya JM, Reme T, Sany J. Serum levels of secretory IgA and in vitro production of IgA in rheumatoid arthritis. Clin Exp Rheumatol 1993; 11, 541-544. Disclosure of Interest: None Declared